Green's relations on semigroups of regressive transformations with restricted range - Sangkhanan K. (2017)
© 2016 Academic Publications, Ltd. Let X' be a subposet of a poset X. Define P RE (X, X') be the semigroup under composition of all regressive transformations from a subset of X into X'. Moreover, T RE (X,X')={α ∈P RE (X,X'):dom α=X}. In 2012, C. Namnak and E. Laysirikul [3] investigated the Green's relations on T RE (X) = T RE (X, X). Now, we aim to extend the result of them by study the Green's relations on the semigroups T RE (X, X') and P RE (X, X').